Facies architecture and reservoir quality of Unit B, Permian Laingsburg Formation, southwestern Karoo Basin, South Africa - Lombard, Donovan Joseph (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.